Examining factors affecting employee's job satisfaction under the practices of human resources management and total quality management: case study of Egyptian petroleum company - Hasan, Lamya Mustafa Muhammad; Muhammad, Sarah Bashir Ali (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
تهدف هذه الدراسة إلى معرفة تأثير ممارسات إدارة الموارد البشرية (HRM) وممارسات إدارة الجودة الشاملة (TQM) على الرضا الوظيفي بناء على عينة من ٣٥٠ موظف في إحدى شركات البترول العاملة في مصر، استخدمت اختبارات الموثوقية والصلاحية والارتباط والانحدار وتحليل عامل الاستكشاف لفحص الفرضيات المقترحة والتحقق من صحتها. تظهر النتائج تباين لممارسات إدارة الموارد البشرية وإدارة الجودة الشاملة بنسبة ۷۹% في الرضا الوظيفي وتظهر أيضا ارتباطا بين إدارة الموارد البشرية وإدارة الجودة الشاملة مع الرضا الوظيفي. بالإضافة إلى ذلك، تظهر النتائج أن أعلى ممارسات ارتباطا بالرضا الوظيفي في إدارة الموارد البشرية هي التدريب والتطوير بقيمة 76ـ0، وأعلى الممارسات ارتباطا بالنسبة إلى ممارسات إدارة الجودة الشاملة هي تمكين الموظف بقيمة 82ـ0. This study aims to investigate the effect of human resources management (HRM) practices and total quality management (TQM) practices on employee's job satisfaction. based on a sample of 350 responses at a petroleum company operating in Egypt, reliability, validity, correlation, regression and exploratory factor analysis tests were used to examine the proposed hypotheses and validate the model. the results show that HRM and TQM practices have a 79% variance in employees' job satisfaction. to add, results show an association between HRM and employees’ job satisfaction and a relation between TQM and employee job satisfaction. furthermore, results show that the highest correlation practices in HRM is training and development, with employee job satisfaction at a value of 0.76. the highest correlation in TQM practices is that of employee empowerment, with a value of 0.82. this study was conducted in Egypt only. the sample was composed of 350 participants, a figure that should be expanded in the future. finally, only four HRM practices were examined, and only five aspects in TQM were tested. this research contributes to practices by developing a model that combines HRM and TQM to test employee job satisfaction in petroleum companies. this study contributes to existing literature by providing a model that combines HRM and TQM with employee job satisfaction. the model attempts to enhance employee satisfaction by testing a given company's HRM and TQM practices.